2020
DOI: 10.1016/j.amsu.2020.07.025
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 pandemic on residency and fellowship training programs in Saudi Arabia: A nationwide cross-sectional study

Abstract: Background Coronavirus disease 2019 (COVID-19) has profoundly impacted residency and fellowship training and education. However, how and to what extent the daily involvement of trainees in clinical and surgical activities was compromised by the COVID-19 pandemic is currently unknown. Materials and methods We conducted an electronic survey. An invitation was sent through the executive training administration of the Saudi Commission for Health Specialties (SCFHS) randomly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
76
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(84 citation statements)
references
References 21 publications
8
76
0
Order By: Relevance
“…In our cohort 48% of residents were trained on how to protect themselves against COVID-19 spread and 48% were trained on how to protect others, this is similar to what was reported in a similar Saudi study in which 43.8% of residents had enough training for the proper use of personal protective equipment (7). This study also reported that 7 participants out of 240 (2.9%) responders were infected with COVID-19 which is lower than what we have reported (17 infected residents out of 255 responders (6.6%)).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In our cohort 48% of residents were trained on how to protect themselves against COVID-19 spread and 48% were trained on how to protect others, this is similar to what was reported in a similar Saudi study in which 43.8% of residents had enough training for the proper use of personal protective equipment (7). This study also reported that 7 participants out of 240 (2.9%) responders were infected with COVID-19 which is lower than what we have reported (17 infected residents out of 255 responders (6.6%)).…”
Section: Discussionsupporting
confidence: 85%
“…In this regard, clinical training programs for medical students and residents have been dramatically affected as they require hands-on interaction with patients which originally takes place in healthcare facilities; mainly hospitals. In a recent study carried out in Saudi Arabia, an 84.6% reduction in training activities was reported in residency training programs (7). In our hospital, King Abdullah University Hospital (KAUH) which is the academic center a liated with Jordan University of Science and Technology (JUST), the impact of the pandemic on residency training programs was further complicated due to the fact that KAUH was designated by the Jordanian Ministry of Health as the main center for treating COVID-19 patients and one of 7 centers performing PCR testing for suspected cases (8).…”
Section: Introductionmentioning
confidence: 97%
“…A nationwide cross-sectional study of residents and fellows in several specialties in SA reported that 84.6% of the respondents reported a reduction in training activities due to the COVID-19 pandemic. 28 The authors of the study recommended the use of e-learning platforms to continue some educational activities. 28 The presence of COVID-19 has accelerated the creative usage of digital communication and dissemination of educational materials.…”
Section: Discussionmentioning
confidence: 99%
“…28 The authors of the study recommended the use of e-learning platforms to continue some educational activities. 28 The presence of COVID-19 has accelerated the creative usage of digital communication and dissemination of educational materials. Social media channels have become instrumental to the future of rheumatology education, with online journal clubs, more opportunities for interactive educational formats, and other benefits.…”
Section: Discussionmentioning
confidence: 99%
“…11 At the same time, this will affect the practice of residents as well as their mental health, as elective cases have been suspended and residency examinations delayed, which will surely have a stressful impact on training residents. 12 Despite all those issues residents were facing because of this pandemic, the training residency program continued. For this reason, Saudi board program members have discussed changes to national health care systems and the impact on otolaryngology residents to initiate a new plan for their residents in response to the COVID-19 pandemic to ensure their safety and provide maximum clinical practice.…”
Section: Discussionmentioning
confidence: 99%